Single vs Multiple Dose of Cefazolin Prophylaxis in Elective Cesarean Section - Purbadi, Sigit; Fadli, Muhamad (Indonesian Socety of Obstetrics and Gynecology, 2017)
Introduction: Caesarean section (CS) is one of port d’ entrée from infection in women and it is related to maternal morbidity during puerpureal period. Until now, there is still lack of consensus regarding prophylactic antibiotic protocol before CS procedure. This study aims to determine the comparative efficacy between single dose and multiple doses of cefazolin prior incision toward the incidence of maternal infection. Methods: This was a single-blind, randomized, clinical trial study with two methods of intervention including 2-gram single dose cefazolin at 30 minutes’ prior incision and 2-gram single dose cefazolin at 30 minutes’ prior incision continued 1-gram cefazolin after 8 hours of procedure. We recruited women undergone elective CS at Fatmawati and Anna Hospital, Jakarta from January to March 2016. The primary outcomes were surgical site infection, urinary tract infection, and endometritis based on clinical findings during 30 days of follow-up period. Results: A total of 46 subjects were recruited which 23 of them were in single dose cefazolin group and the other 23 subjects were in multiple dose of cefazolin group. There were 9 subjects having infection (19.6%). There was no statistical difference in the incidence of infection between two groups (p=1.00; relative risk 0.80, 95% CI 0.25-2.61). Conclusion: Single dose of cefazolin shows similar rates of infection incidence to multiple dose. Therefore, single dose of cefazolin can be a protocol in CS based on its efficacy and efficiency. [Indones J Obstet Gynecol 2017; 5-1: 60-65] Keywords: cefazolin, maternal infection, multipe dose, single dose